ORAL MUCOADHESIVE MICROCARRIERS FOR CONTROLLED AND EXTENDED RELEASE FORMULATIONS: Pharmaceutical Science-Pharmaceutics - ATHAR ALLI, SAIKH MAHAMMED; AJHAR ALI, SAIKH MAHAMMED; FATMAH, KANIJ; YASMIN FATMAH, NARGISH (International Journal of Life Science and Pharma Research, 2011)
Nowadays oral mucoadhesive microcarriers were exploited extensively to improve the performance of delivery system and the patient compliance through controlling and extending release profile of drug. Present review work is aimed to explore the aspects of mucoadhesives, development and evaluation techniques of mucoadhesive microcarriers that will aid in designing an efficient extended release oral mucoadhesive microcarrier system. Data revealing several aspects like advantages, development and evaluation techniques of microcarrier systems; and properties of mucoadhesives influencing development and performance of microcarriers; were collected from databases, compiled and analysed. Presented data will help pharmaceutical scientists engaged in designing dosage forms for enhancing the bioavailability of drug(s) and performance of delivery system. Oral mucoadhesive microcarriers were having potentiality for controlling and extending release profile so as to improve performance and patient compliance.